PERBANDINGAN TINGKAT NYERI PADA PASIEN TERPASANG VENTILASI MEKANIK SELAMA ISTIRAHAT DAN TINDAKAN KEPERAWATAN RUTIN DI RUANG INTENSIVE CARE UNIT RUMAH SAKIT PUSAT PERTAMINA - Dewi, Nur Sari; Anggraeni, Diah Tika (Jurnal Keperawatan Widya Gantari Indonesia, 2022)
Pain is the most common stressor experienced by patients in the ICU. Nearly 5 million patients are treated in the Intensive Care Unit (ICU), and 71% experience pain during treatment. Most of the pain felt by patients in the ICU is when the patient is mechanically ventilated. Pain can occur during routine nursing actions such as positioning, suction, and oral hygiene. This study aims to compare the level of pain in patients on mechanical ventilation during rest and routine nursing actions in the Intensive Care Unit of Pertamina Central Hospital. This research is an analytical observational research design with a cross-sectional approach, a sample of 31 patients with mechanical ventilation installed and the sampling technique used is non-probability sampling with accidental sampling. Data were taken using the Critical Pain Observation Tool (CPOT) questionnaire to measure pain levels. The results showed that there was a comparison of pain levels during rest and positioning with a comparison value of 15.00 (p<0.05); There is a comparison of pain levels during rest and suction action with a comparison value of 15.00 (p<0.05); There is a comparison of pain levels during rest and oral hygiene measures with a comparison value of 7.00 (p <0.05).